Antagonizing dabigatran by idarucizumab in cases of ischemic stroke or intracranial hemorrhage in Germany: a national case collection - Kermer, Pawel; Held, Valentin; Purrucker, Jan; Ringleb, Peter A. (International journal of stroke, 2017)
BackgroundIdarucizumab is a monoclonal antibody fragment with high affinity for dabigatran that reverses its anticoagulant effects within minutes. It may exhibit the potential for patients under dabigatran therapy suffering ischemic stroke to regain eligibility for thrombolysis with rt-PA and may inhibit lesion growth in patients with intracerebral hemorrhage on dabigatran.AimsTo provide insights into the clinical use of idarucizumab in patients under effective dabigatran anticoagulation presenting with signs of ischemic stroke or intracranial hemorrhage.MethodsRetrospective data collected from German neurological/neurosurgical departments administering idarucizumab following product launch from January to August 2016 were used.ResultsThirty-one patients presenting with signs of stroke received idarucizumab in 22 stroke centers. Nineteen patients treated with dabigatran presented with ischemic stroke and 12 patients suffered from intracranial bleeding. In patients receiving rt-PA thrombolysis following idarucizumab, 79% benefitted from i.v. thrombolysis with a median improvement of five points in NIHSS. No bleeding complications occurred. Hematoma growth was observed in 2 out of 12 patients with intracranial hemorrhage. The outcome was favorable with a median NIHSS improvement of 5.5 points and mRS 0?3 in 67%. Overall, mortality was low with 6.5% (one patient in each group).ConclusionAdministration of rt-PA after reversing dabigatran activity with idarucizumab in case of ischemic stroke is feasible, easy to manage, effective, and appears to be safe. In dabigatran-associated intracranial hemorrhage, idarucizumab has the potential to prevent hematoma growth and improve outcome. Idarucizumab represents a new therapeutic option for patients under dabigatran treatment presenting with ischemic stroke or intracranial hemorrhage.